SPATIAL MOVEMENTS AS A PLOT CREATING ELEMENT OF DIANA JONES’ FAIRY NARRATIVE “HOWL’S MOVING CASTLE” - Martynets, A. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article makes an attempt of the analysis of spatial movements represented in D. Jones’ fantasy work “Howl’s Moving Castle” on the level of text plot creating. The researches into the problems of the chronotope by M. Bakhtin, N. Kopystians’ka and S. Skwarczyńska are taken into consideration.